Chlorogenic Acid Inhibits Human Glioma U373 Cell Progression via Regulating the SRC/MAPKs Signal Pathway: Based on Network Pharmacology Analysis - Zhou J; Zhang F; Chen J; Zhang S; Wang H (Dove Medical Press, 2021)
Jiabin Zhou,1,* Fengqi Zhang,2,* Jun Chen,3 Shilin Zhang,4 Haijun Wang1 1Department of Neurosurgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Department of Neurosurgery, Xiangya Hospital, Central South University, Changsha, 410008, People’s Republic of China; 3Department of Neurosurgery, Traditional Chinese Hospital of LuAn, LuAn, Anhui Province, 237006, People’s Republic of China; 4Aviation Medical Support Center, Naval Aviation University of Chinese People’s Liberation Army, Yantai, Shandong Province, 264001, People’s Republic of China*These authors contributed equally to this workCorrespondence: Haijun WangDepartment of Neurosurgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1277 Jiefang Road, Wuhan, 430022, People’s Republic of ChinaEmail whj11260@163.comIntroduction: Chlorogenic acid (CGA) is a type of polyphenolic substance that is widely extracted from many traditional Chinese medicines (eg, Lonicera japonica Thunb, Eucommia ulmoides Oliver) and exhibits a wide range of anti-tumor effects. However, the potential molecular mechanisms of CGA in glioma U373 cells remain unclear.Methods: Network pharmacology analysis was used to explore the potential therapeutic targets of CGA in glioma. Human glioma U373 cells were treated with different concentrations of CGA for 24 h. CCK-8 assays were used to detect the inhibitory rate of cell growth. Annexin V-FITC/PI staining and Hoechst 33342 staining were used to detect apoptosis. PI staining was used to investigate cell-cycle progression. Wound healing assays and transwell assays were used to detect the cell migration and invasion, respectively. Western blotting and immunohistochemistry were used to measure protein levels in vitro and in vivo.Results: The proliferation of U373 cells was significantly inhibited by CGA in a dose- and time-dependent manner. CGA significantly arrested the cell cycle of U373 cells in the G2/M phase and induced apoptosis. Moreover, CGA significantly suppressed the migration and invasion of U373 cells. Additionally, we found that CGA inhibited the growth of U373 cells in vivo. Furthermore, network pharmacology analysis suggested that the anti-tumor effects of CGA on U373 cells were associated with the down-regulation of the SRC/MAPKs signaling pathway.Discussion: The present study indicated that CGA had anti-glioma effects on U373 cells by down-regulating SRC/MAPKs signal pathway.Keywords: chlorogenic acid, apoptosis, migration and invasion, network pharmacology, SRC/MAPKs signal pathway